Theorizing Homophobia - Adam, Barry D. (Sexualities, 1998)
A series of contemporary theories that have been used to explain homophobia are assessed. Structural, feminist, comparative, gender panic, queer, and socio-historical theories rely on the premises of a diverse set of scholarly disciplines, and in turn, generate their own objects of analysis, whether `homophobia', `heterosexism', or `heteronormativity'. While the current flourishing of gay and lesbian studies has generated important insights into the workings of homophobia, analyses have also tended to be limited and fragmentary. This paper suggests a study of homophobic projects that combines theoretical tools able to recognize experience, discourse, structure, and history.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Looking queer: body image and identity in lesbian, bisexual, gay, and transgender communities - Atkins, Dawn (Haworth Press, 1998)
Looking Queer: Body Image in Lesbian, Bisexual, Gay, and Transgender Communities contains research, firsthand accounts, poetry, theory, and journalistic essays that address and outline the special needs of sexual minorities when dealing with eating disorders and appearance obsession. Looking Queer will give members of these communities hope, insight, and information into body image issues, helping you to accept and to love your body. In addition, scholars, health care professionals, and body image activists will not only learn about queer experiences and identity and how they affect individuals, but will also understand how some of the issues involved affect society as a whole. Dismantling the myth that body image issues affect only heterosexual women, Looking Queer explores body issues based on gender, race, class, age, and disability. Furthermore, this groundbreaking book attests to the struggles, pain, and triumph of queer people in an open and comprehensive manner. More than 60 contributors provide their knowledge and personal experiences in dealing with body image issues exclusive to the gay and transgender communities, including: exploring and breaking down the categories of gender and sexuality that are found in many body image issues finding ways to heal yourself and your community discovering what it means to “look like a dyke” or to “look gay” fearing fat as a sign of femininity determining what race has to do with the gay ideal discussing the stereotyped ”double negative”--being a fat lesbian learning strategies of resistance to societal ideals critiquing ”the culture of desire” within gay men’s communities that emphasizes looks above everything else Revealing new and complex dimensions to body image issues, Looking Queer not only discusses the struggles and hardships of gay, lesbian, bisexual, and transgendered persons, but looks at the processes that can lead to acceptance of oneself. Written by both men and women, the topics and research in Looking Queer offer insight into the lives of people you can relate to, enabling you to learn from their experiences so you, too, can find joy and happiness in accepting your body.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; image corporelle; intersectionnalité; premier cycle; queer; régions géographiques; sciences humaines; soc2014; thématiques; troubles alimentaires; états-unis

Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Homos: repenser l'identité - Bersani, Leo (Odile Jacob, 1998)
A travers l'étude notamment de la "queer theory" de M. Foucault et de la psychanalyse, de la politique du sadomasochisme et de l'image du hors-la-loi gay chez Proust, Gide et Genet, l'auteur propose une réflexion critique sur l'identité homosexuelle et les dangers du repli communautaire. C'est aussi une introduction aux débats autour des "gays studies" qui, après les USA, se développent en Europe
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; foucault; genet; gide; identités LGBTQIA2+; premier cycle; proust; queer; soc2014; thématiques; études gaies et lesbiennes; études littéraires

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Collection Les Entêtées, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

L’écriture au féminin existe-t-elle? - Bordeleau, Francine (Lettres québécoises, 1998)
Keywords: amériques; cours; discipline; fem1000; premier cycle; québec; ressource en ligne; régions géographiques; thématiques; écriture des femmes*; études littéraires

Femmes au miroir: une histoire de l'autoportrait féminin - Borzello, Frances (Thames & Hudson, 1998)
Une sélection d'autoportraits féminins empruntés à toute l'histoire de l'art, de la religieuse anonyme qui glissa son effigie dans la lettrine d'un manuscrit du XIIe siècle à Cindy Sherman et ses photogrammes révélateurs des visions stéréotypées de la femme, en passant par Sofonisba Anguissola, Artemisia Gentileschi, Elisabeth Vigée-Lebrun, Frida Kahlo, Hannah Wilke, etc.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

La domination masculine - Bourdieu, Pierre (Collection Liber, 1998)
Difficile de remettre en question la domination masculin tellement elle est ancrée dans nos inconscients et accordée à nos attentes. Partant d'une description ethnographique de la société kabyle, Pierre Bourdieu explore les structures symboliques de cet inconscient et rocentrique qui survit chez les hommes et les femmes d'aujourd'hui
Keywords: 1900-1999; approches et analyses; cours; cycles supérieurs; discipline; division sexuelle du travail; europe; fem1000; fem7000; france; lit3220; lit3495; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail

Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

La conquête d'un espace public : les bars fréquentés par les lesbiennes - Chamberland, Line (Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; his4860; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; montréal; premier cycle; québec; rapports sociaux de sexe; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences

La pensée "queer" et la déconstruction du sujet lesbien - Chamberland, Line (1998)
Par son refus radical de tout système de catégories identitaires de même que de toute stratégie politique, théorique ou épistémologique qui se réclame d’un tel positionnement, le courant queer remet en question la base identitaire du mouvement des lesbiennes qui s’est constitué depuis plus d’une vingtaine d’années et déstabilise les perspectives féministes qui ont prévalu jusqu’à récemment dans la théorisation du lesbianisme. Dans cette communication, j’aimerais discuter, en tant que sociologue et féministe, certains enjeux soulevés par la pensée queer quant à la (dé)construction du sujet lesbien. En effet, une fois admis le caractère multiple et fragmenté des subjectivités individuelles, quels outils ce courant fournit-il pour penser la diversité parmi les lesbiennes et explorer concrètement les intersections entre sexualité, genre, ethnie et classe ? Alors que le lesbianisme féministe a défini le sujet lesbien comme une identité de genre et comme lieu d’une résistance politique à la domination patriarcale, l’approche dite queer ne risque-t-elle pas d’occulter de nouveau les rapports de sexe en assimilant les unes aux autres les multiples formes de transgressions sexuelles, y inclus le lesbianisme ?
Keywords: amériques; approches et analyses; cours; cycles supérieurs; fem1000; fem9000; genre; identités; identités LGBTQIA2+; lesbianisme; premier cycle; queer; québec; ressource en ligne; régions géographiques; thématiques

Feminism and ecological communities: an ethic of flourishing - Cuomo, Chris J. (Routledge, 1998)
Feminism and Ecological Communities presents a bold and passionate rethinking of the ecofeminist movement. It is one of the first books to acknowledge the importance of postmodern feminist arguments against ecofeminism whilst persuasively preseenting a strong new case for econolocal feminism. Chris J.Cuomo first traces the emergence of ecofeminism from the ecological and feminist movements before clearly discussing the weaknesses of some ecofeminist positions. Exploring the dualisms of nature/culture and masculing/feminine that are the bulwark of many contemporary ecofeminist positions and questioning traditional traditional feminist analyses of gender and caring, Feminism and Ecological Communities asks whether women are essentially closer to nature than men and how we ought to link the oppression of women, people of colour, and other subjugated groups to the degradation of nature. Chris J.Cuomo addresses these key issues by drawing on recent work in feminist ethics as well as teh work of diverse figures such as Aristotle, John Dewey, Donna Haraway adn Maria Lugones. A fascinating feature of the book is the use of the metaphor of the cyborg to highlight the fluidity of the nature/culture distinction and how this can enrich econfeminist ethics and politics. An outstanding new argument for an ecological feminism that links both theory and practice, Feminism and Ecological Communities bravely redraws the ecofeminist map. It will be essential reading for all those interested in gender studies, environmental studies and philosophy.
Keywords: approches et analyses; com5170; cours; discipline; environnement; philosophie; postmodernisme; premier cycle; sciences humaines; thématiques; écoféminisme

Essentialism vs. social constructionism in the study of human sexuality - DeLamater, John D.; Hyde, Janet Shibley (The Journal of Sex Research, 1998)
According to classical essentialism, there are underlying true forms or essences, there is discontinuity between different forms rather than continuous variation, and these true forms are constant over time. Modern essentialism consists of a belief that certain phenomena are natural, inevitable, and biologically determined. We consider sociobiology, evolutionary psychology, genetic research, brain research, and endocrine research as examples of essentialist approaches, focusing particularly on how these research approaches treat sexual orientation and sexual attraction. Social constructionism, in contrast, rests on the belief that reality is socially constructed and emphasizes language as an important means by which we interpret experience. We briefly review social constructionist research on sexual orientation and sexual attraction. Finally, we review examples of conjoint or interactionist research, uniting biological and social influences. We conclude that, although there may be theories and research that conjoin biological and social influences, there can be no true conjoining of essentialism and social constructionism.
Keywords: approches et analyses; comparaison; construction sociale; cours; discipline; essentialisme; histoire et politique; méthodologie; postmodernisme; premier cycle; sciences humaines; sex2283; sociologie; thématiques

Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank William (Des hommes et des femmes en changement, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; violences

Le projet féministe à l’aube du XXIe siècle : un projet de libération et de solidarité qui fait toujours sens - Descarries, Francine (Cahiers de recherche sociologique, 1998)
En situant les rapports de genre au cœur de leur élaboration conceptuelle et en inscrivant leur transformation comme un enjeu stratégique, les études féministes se sont progressivement imposées dans l'univers des sciences humaines comme une approche critique et comme une problématique du changement. Après une revue des trois grands courants de pensée qui se sont développés au sein et en marge du mouvement féministe au cours des dernières décennies, l'auteure se demande si la pensée féministe, ou plutôt les différents courants de la pensée féministe actuelle sont encore engagés dans ces mêmes fins. Sont-elles encore capables de contribuer au renouvellement des savoirs, de proposer un projet de société original, et d'imaginer les termes d'un nouveau contrat entre les genres ? Sont-elles capables de nourrir une lutte féministe unie, une politique de coalition ouverte à la diversité et à la différence, mais qui ne perd rien de sa cohésion et de sa force de ralliement ? Ces questions servent de pistes thématiques pour la discussion de l'auteur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; approches et analyses; cours; discipline; fem1000; féminisme matérialiste; histoire et politique; justice sociale; militance; mouvements des femmes*; mouvements féministes; occident; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; thématiques

Des parents du même sexe - Dubreuil, Eric (O. Jacob, 1998)
A travers le témoignage de 29 personnes dont 7 enfants et adolescents, une incursion dans le paysage des familles "homoparentales". Bousculant le cadre traditionnel de la famille, ces structures posent, par leur démarche même, des questions sur des sujets aussi essentiels que la filiation, l'adoption, la procréation médicalement assistée, allant bien au-delà de l'homosexualité.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexisme; identités LGBTQIA2+; justice reproductive; maternité; parentalité; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Politiques de l'histoire: Gay New York et l'historiographie homosexuelle aux États-Unis - Fassin, Éric (Actes de la recherche en sciences sociales, 1998)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques; états-unis

Le genre : assez fort pour lui, mais conçu pour elle - Garneau, Édith (Politique et Sociétés, 1998)
Cet article vise à examiner la manière dont certaines théoriciennes féministes américaines, anglo-saxonnes, françaises et québécoises ont conceptualisé les concepts ambigus de sexe et de genre. Il présente les idées nouvelles et complexes de Joan Scott, Seyla Benhabib et Iris Marion Young et a pour but de permettre et de faire valoir d’autres façons pour les politologues et les féministes de conceptualiser le genre.
Keywords: 1900-1999; cours; discipline; fem1000; genre; identités LGBTQIA2+; occident; premier cycle; périodes historiques; ressource en ligne; science politique; science politique et droit; thématiques

Female masculinity - Halberstam, Jack (J.) (Duke University Press, 1998)
Dans cet ouvrage essentiel de la théorie queer, Jack Halberstam s’attaque au statut protégé de la masculinité masculine et montre que la masculinité féminine lui offre une alternative distincte depuis plus de deux siècles. Démontrant que la masculinité féminine n’est pas une mauvaise imitation de la virilité, mais une mise en scène vivante et dramatique de genres hybrides et minoritaires, Halberstam catalogue la diversité des expressions de genre chez les femmes masculines, depuis les pratiques pré-lesbiennes du XIXe siècle jusqu’aux performances contemporaines des drag kings.
Keywords: amériques; approches et analyses; cours; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans*; premier cycle; queer; régions géographiques; sciences humaines; thématiques; états-unis

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

Les limites de l'identité sexuelle - Lamoureux, Diane (Itinéraires féministes, 1998)
Les études de Michel Foucault sur la sexualité et son histoire, de même que les premiers travaux de Judith Butler sur la fluidité des postures de genre, ont contribué à l’émergence de la pensée queer, qui récuse le fixisme identitaire sans pour autant rejeter la notion d’identité. Ce courant de pensée a eu des répercussions tant dans le domaine des études féministes que dans celui des études LGBT ou encore des études sur les sexualités qui s’intéressent aux marges de la société hétérosexiste. Au-delà des oppositions binaires du masculin et du féminin ou de l’hétérosexualité et de l’homosexualité, il y a toujours un indécidable, qui résiste à la bipartition, une zone de flou, d’hybride et de poreux. C’est cet indécidable qui force la réflexion, non pas pour le faire entrer dans une catégorie d’opposition binaire, mais pour faire rebondir la pensée. Des textes de Carmen Gill, Ross Higgins, Diane Lamoureux, Marie-José Nadal, Tania Navarro Swain, Paul-André Perron, Robert Schwartzwald et Colette St-Hilaire.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; europe; fem1000; france; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques

Le sexe du savoir - Le Doeuff, Michèle (Aubier, 1998)
Le savoir est-il l'apanage du sexe masculin? L'auteur, chargée de recherches au CNRS, fait ici la généalogie des mythes qui sexualisent le savoir et donc le pouvoir. Sur un ton polémique et drôle, elle propose un parcours original dans l'histoire de la philosophie et de la littérature, mais aussi dans l'actualité.
Keywords: approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; misogynie; philosophie; premier cycle; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Colonialism/postcolonialism - Loomba, Ania (Routledge, 1998)
Colonialism/Postcolonialism est un guide complet mais accessible sur les dimensions historiques, théoriques et politiques des études coloniales et postcoloniales. Ania Loomba examines the key features of the ideologies and history of colonialism, and the relationship of colonial discourse to literature. She goes on to consider the challenges to colonialism, surveying anti-colonial discourses, and recent developments in postcolonial theories and histories. Looking at how sexuality is figured in the texts of colonialism, Colonialism/Postcolonialism shows how contemporary feminist ideas and concepts intersect with those of postcolonialist thought
Keywords: approches et analyses; arts; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; ressource en ligne; thématiques; études littéraires

Écoféminisme - Mies, Maria; Shiva, Vandana (L'Harmattan, 1998)
Est-il possible de créer un nouvel internationalisme, sous la bannière du féminisme et de l'écologie ? La quête d'identité et de différence peut-elle être une plate-forme de résistance à la violence de la mondialisation de l'économie ? Deux femmes, confrontées aux mêmes questions fondamentales sur le sort des générations futures et de la survie de notre planète, l'une avec le regard venant du Sud, l'autre vivant " au cœur de la bête " dans le Nord, se démarquent radicalement de la pensée unique.
Keywords: approches et analyses; com5170; cours; fem1000; histoire et politique; pouvoir; pratiques féministes; premier cycle; ressource en ligne; thématiques; écoféminisme

Pourquoi nous avons écrit ce livre ensemble - Mies, Maria; Shiva, Vandana (Ecoféminisme, 1998)
Keywords: approches et analyses; cours; fem1000; pouvoir; pratiques féministes; premier cycle; ressource en ligne; écoféminisme

Le regard de l'autre: artistes canadiens blancs -- sujets féminins noirs = Through an-other's eyes : white Canadian artists -- black female subjects - Nelson, Charmaine; Robert McLaughlin Gallery (Robert McLaughlin Gallery, 1998)
Catalogue d'une exposition tenue du 11 février au 11 avril 1999 à la Robert McLaughlin Gallery, Oshawa, Ont., du 18 juin au 15 août 1999 à la Thames Art Gallery, Chatam, Ont., du 11 janvier au 13 février 2000 à la Galerie d'art Leonard et Bina Ellen, Université Concordia, Montréal et du 16 septembre au 19 novembre 2000 à la Art Gallery of Nova Scotia, Halifax, N.-É.
Keywords: afro-féminisme; amériques; approches et analyses; canada; cours; féminisme afroaméricain; har4610; histoire et politique; premier cycle; représentation des femme*; représentation des femmes* racisées; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

L’économie politique du sexe : transactions sur les femmes et systèmes de sexe/genre - Rubin, Gayle (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 1998)
La littérature sur les femmes — tant féministe qu’antiféministe — est une longue rumination quant à la nature et à la genèse de leur oppression et de leur subordination sociale. La question n’est pas sans importance, car les réponses qui lui sont données déterminent la manière dont nous envisageons l’avenir et si nous jugeons réaliste ou non d’espérer une société égalitaire entre les sexes. Plus important, l’analyse des causes de l’oppression des femmes fonde toute estimation de ce qu’il faudrait exactement changer pour réaliser une société sans hiérarchie de genre
Keywords: 1900-1999; 1960-1969; 1970-1979; anthropologie; approches et analyses; capitalisme; classe ouvrière; cours; discipline; europe; famille; fem1000; france; féminisme matérialiste; histoire et politique; inégalités; marxisme; patriarcat; premier cycle; psychanalyse; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences; sciences humaines; soc1016; soc2014; sociologie; systèmes d'oppressions; thématiques; théories féministes

À quoi peut servir l'imagination : Olympe de Gouges et la Révolution française - Scott, Joan Wallach (La citoyenne paradoxale : les féministes françaises et les droits de l'homme, 1998)
Analyse d'un autre paradoxe à la française : le modèle républicain fondé sur l'égalité et la liberté de la personne, mise au service de l'exclusion politique des femmes, qui n'ont obtenu le droit de vote qu'en 1944. Ce livre traite de la protestation féministe contre cette prétendue universalité des droits, qui excluait les femmes de la citoyenneté.
Keywords: 1700-1799; citoyenneté; cours; discipline; droits des femmes*; europe; fem1000; france; histoire; histoire et politique; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques

La citoyenne paradoxale : les féministes françaises et les droits de l'homme - Scott, Joan Wallach (Bibliothèque Albin Michel de l'histoire, 1998)
Alors que le débat sur la parité divise les milieux politiques, le féminisme, au-delà de la revendication égalitaire, devrait contribuer à une réévaluation de l'histoire des doctrines et des institutions de la République. Joan W. Scott, personnalité marquante de l'historiographie américaine et professeur à l'Institute for Advanced Study de Princeton, entend montrer comment l'histoire du féminisme, qui fait partie intégrante de l'histoire politique, sert de révélateur aux fondements réels du républicanisme. Les combats d'Olympe de Gouges, Jeanne Deroin, Hubertine Auclert et Madeleine Pelletier, par l'écart de leurs critiques, font apparaître les contradictions d'une théorie universelle des droits de l'homme mise au service de l'exclusion politique des femmes, Joan W. Scott, recourant au concept de gender, trop souvent incompris et caricaturé en France, analyse les différents contextes de ces luttes féministes prises dans les limites de l'héritage politique de la Révolution. Elles n'ont pu réussir, même aujourd'hui, à couper tout à fait le lien identifiant l'individu au masculin. Pour abolir les effets politiques de la différence. D'où le dilemme : soit revendiquer l'égalité au nom de l'individu (neutre et abstrait), soit définir une pertinence politique de la différence sexuelle sans briser l'universalité des droits. Ainsi, ce livre, repérant ce paradoxe au cœur de l'histoire du féminisme, devient une invitation à repenser les principes mêmes du modèle républicain.
Keywords: 1700-1799; citoyenneté; cours; droits des femmes*; europe; fem1000; france; histoire du féminisme; premier cycle; périodes historiques; régions géographiques; thématiques

Only the Literal: The Contradictions of Anti-pornography Feminism - Segal, Lynne (Sexualities, 1998)
Within feminism, battles over pornography have become the wars without end. Despite the controversy it generates, the discourses of anti-pornography feminism have continued to make inroads into legal frameworks, most recently in Canada. This piece surveys the growth and questionable appeal of such feminist campaigning, under the theoretical leadership of Catharine MacKinnon: its rewriting of feminist theory; its parasitic relation to the authoritative, phallocentric discourses of gender and sexuality; its alliance with the most reductive, behaviouristic psychology; its disavowel of fantasy and psychic life; its provocative mirroring of both the style and content of the `pornography' it deplores; its unwavering pursuit of legal remedies which enhance the power of state regulation of sexuality; its threat to subversive expressions of women's sexual agency and repudiation of any possibilities for sexual resignifications.
Keywords: cours; discipline; droits des femmes*; histoire et politique; militance; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques

Crise et mutation du dispositif de la différence des sexes : regard sociologique sur l'éclatement de la catégorie sexe - St-Hilaire, Colette (Les limites de l'identité sexuelle, 1998)
Keywords: 1900-1999; 1990-1999; amériques; cours; cycles supérieurs; différence des sexes; discipline; fem1000; fem7000; lit3220; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."--BOOK JACKET.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis

La construction sociale de l'inégalité des sexes. Des outils et des corps - Tabet, Paola (Bibliothèque du féminisme, 1998)
Aujourd'hui encore, on pense que des contraintes naturelles liées aux capacités reproductives des femmes déterminent leur place dans la société et contribuent à justifier la division du travail entre les sexes. A partir de données sociologiques, ethnologiques et historiques Paola Tabet s'attache à décrire la construction sociale des contraintes dites naturelles qui assignent leur place aux femmes.
Keywords: 1900-1999; anthropologie; cours; discipline; division sexuelle du travail; europe; fem1000; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; thématiques; théories féministes; travail

Histoire comparee de l'homosexualite en Allemagne, en Angleterre et en France dans I'entre-deux guerres - Tarnagne, F. (ACTES DE LA RECHERCHE EN SCIENCES SOCIALES, 1998)
Keywords: 1900-1999; allemagne; angleterre; cours; discipline; entre-deux guerres; europe; france; his4860; histoire; histoire et politique; homosexualité; premier cycle; première guerre mondiale; royaume-uni; régions géographiques; sciences humaines; seconde guerre mondiale; sexualité; sexualités dissidentes; thématiques

African American women in the struggle for the vote, 1850-1920 - Terborg-Penn, Rosalyn (Indiana University Press, 1998)
Keywords: afro-féminisme; amériques; approches et analyses; cours; droits des femmes*; fem3100; féminisme afroaméricain; premier cycle; ressource en ligne; régions géographiques; thématiques; états-unis

Les courants de pensée féministe - Toupin, Louise (L’R des centres de femmes du Québec, 1998)
Les courants de pensée féministe Dans ce document - aussi offert en format PDF - Louise Toupin met en évidence trois grandes traditions de pensée féministe qui sont autant de points de repères qui aident à comprendre l’évolution des diverses tendances féministes. Elle décrit les traditions du féminisme libéral, du féminisme marxiste et du féminisme radical et traite des métamorphoses qu’elles ont connues ainsi que des perspectives nouvelles qui les ont traversées.
Keywords: 1900-1999; cours; discipline; fem1000; histoire et politique; mouvements féministes; occident; premier cycle; périodes historiques; ressource en ligne; sciences humaines; sex3383; sofia; thématiques; théories féministes

L'art de la récupération des médias dans Médias et féminismes: minoritaires sans paroles - Yamani, Myriame el (Médias et féminismes: minoritaires sans paroles, 1998)
Les médias, s'ils informent, ne servent plus à communiquer. C'est pourquoi cet essai veut répondre à une double question : comment et pourquoi les minoritaires, et les femmes en particulier, s'ils prennent parfois la parole dans le champ médiatique en créant leurs propres journaux, ne peuvent pas la garder ? Comment et pourquoi les médias majoritaires ne rendent-ils pas compte de ces points de vue de minoritaires, en particulier lors d'événements qui les concernent ?
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; canada; cours; discipline; médias; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail social; trs1205